2022
DOI: 10.3390/met12020219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sintering Temperature on the Structural, Morphological, and Electrochemical Properties of NiO-YSZ Anode Synthesized by the Autocombustion Route

Abstract: In this study, nickel oxide–Y2O3-doped ZrO2 (NiO-YSZ) composite powder as an anode material was synthesized using a cost-effective combustion method for high-temperature solid oxide fuel cell (SOFC). Further, the effects of sintering temperatures (1200, 1300, and 1400 °C) were studied for its properties in relation to the SOFC performance. The prepared and sintered NiO-YSZ materials were characterized for their surface morphology, composition, structure, and conductivity. The cubic crystalline nature of NiO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The sharp peaks are attributed to the enhancement of the crystallinity, which is important for improving the electrochemical performance of the LASO SE. 40 The XRD patterns of electrolytes sintered at temperatures of 750 °C or higher matched that of the single-phase LiAlSiO 4 phase (ICSD: 2929), but the electrolytes sintered at 700 °C or lower temperatures contained trace amounts of LiAlO 2 impurities. 41−43 These results confirmed that oxygen and silicon atoms combined during sintering at low temperatures (≤700 °C), which is undesirable.…”
Section: Optimization Of Sintering Temperature Of the Laso Electrolyt...mentioning
confidence: 99%
“…The sharp peaks are attributed to the enhancement of the crystallinity, which is important for improving the electrochemical performance of the LASO SE. 40 The XRD patterns of electrolytes sintered at temperatures of 750 °C or higher matched that of the single-phase LiAlSiO 4 phase (ICSD: 2929), but the electrolytes sintered at 700 °C or lower temperatures contained trace amounts of LiAlO 2 impurities. 41−43 These results confirmed that oxygen and silicon atoms combined during sintering at low temperatures (≤700 °C), which is undesirable.…”
Section: Optimization Of Sintering Temperature Of the Laso Electrolyt...mentioning
confidence: 99%
“…Sr 0.95 Fe 0.9 Mo 0.1 O 3−δ (SFM) and Sr 0.95 Fe 0.8 Mo 0.1 Ni 0.1 O 3−δ (SFMN) catalysts were synthesized via a typical glycine-citric acid combustion method, similar to that in the literature [31][32][33]. All the chemicals were purchased from Sinopharm Chemical Reagent Co., Ltd (Shanghai, China).…”
Section: Experiments 21 Materials Synthesismentioning
confidence: 99%
“…Solid oxide fuel cell (SOFC) is a promising power generation technology [1][2][3]. It efficiently converts chemical energy into electrical energy and reduces pollutant gas emissions compared to conventional power generation technologies.…”
Section: Introductionmentioning
confidence: 99%